Impact of Metabolic Dysfunction-Associated Fatty Liver Disease of Varying Severity on Antiviral Treatment Outcomes and Clinical Prognosis in Patients with Chronic Hepatitis B: A Systematic Review and Meta-analysis - Qianqian Zhu; Chengde Su; Mingdan Li; Yali Xu; Qian Liu; Ying Zhang; Xinyi Zhang; Qiuxiang Li; Huajun Wang; Yawen Luo; Ping Yang (Infectious Diseases and Therapy)
Abstract Introduction The coexistence of hepatitis B virus (HBV) infection and metabolic dysfunction-associated fatty liver disease (MAFLD) is becoming increasingly common. The bidirectional interaction between persistent HBV infection and lipotoxicity may influence the progression of the disease. However, to date, there has been a lack of meta-analyses that stratify this dual-disease population based on the severity of MAFLD. Methods This study was conducted in accordance with the PRISMA guidelines. Relevant literature on chronic hepatitis B (CHB) coexisting with MAFLD, published in Chinese and English databases from inception to January 6, 2025, was systematically retrieved. A meta-analysis was performed to evaluate the impact of MAFLD of varying severity on the efficacy of antiviral therapy and clinical outcomes in patients with CHB. Results A total of 24 studies were included, among which seven investigated the impact of MAFLD severity on antiviral treatment efficacy, and 17 explored the influence of MAFLD on clinical outcomes in CHB. The meta-analysis revealed the following: HBeAg seroclearance rate: For the mild MAFLD group versus the CHB-only group, the odds ratio (OR) was 0.62; for the moderate-to-severe MAFLD group versus the CHB-only group, OR = 0.37, indicating a more pronounced negative impact of moderate-to-severe MAFLD on HBeAg seroconversion. HBsAg seroclearance rate: For the mild MAFLD group versus the CHB-only group, OR = 0.43; for the moderate-to-severe MAFLD group versus the CHB-only group, OR = 0.20, further supporting the greater adverse effect of more severe MAFLD on HBsAg seroclearance. Incidence of hepatocellular carcinoma (HCC): For the CHB combined with MAFLD group versus the CHB-only group, OR = 1.77, demonstrating a markedly increased risk of HCC development in the CHB combined with MAFLD group compared to the CHB-only group. Conclusions This study is the first to systematically examine the complex relationship between CHB and MAFLD from the perspective of hepatic steatosis severity stratification. CHB combined with moderate-to-severe MAFLD is associated with HBsAg/HBeAg seroclearance rate and the likelihood of achieving functional cure, suggesting that MAFLD may exert a potentially beneficial effect on antiviral therapy. However, MAFLD is also significantly associated with an increased risk of HCC, potentially accelerating hepatic carcinogenesis through lipotoxic pathways.